2020
DOI: 10.1021/acs.analchem.0c03822
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Detection Platform of Disease Biomarkers Based on Recombinase Polymerase Amplification with H-Sandwich Aptamers

Abstract: The detection of trace protein biomarkers is essential in the diagnostic field. Protein detection systems ranging from widely used enzyme-linked immunosorbent assays to simple, inexpensive approaches, such as lateral flow immunoassays, play critical roles in medical and drug research. Despite continuous progress, current systems are insufficient for the diagnosis of diseases that require high sensitivity. In this study, we developed a heterogeneous sandwich-type sensing platform based on recombinase polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Although far less common than S protein aptamers, aptamers for the N protein of SARS‐CoV‐2 have also been discovered. At present, three SELEX studies have been reported (Table 3 and Table S5) [88–90] …”
Section: Aptamers For the N Protein Of Sars‐cov‐2mentioning
confidence: 99%
“…Although far less common than S protein aptamers, aptamers for the N protein of SARS‐CoV‐2 have also been discovered. At present, three SELEX studies have been reported (Table 3 and Table S5) [88–90] …”
Section: Aptamers For the N Protein Of Sars‐cov‐2mentioning
confidence: 99%
“…A COVID-19 diagnostic approach that integrates RT-RPA and universal lateral flow test strips into an individual microfluidic chip has been reported with fast, highly sensitive, 30-min acquisition results [ 55 ]. Kang et al [ 56 ] reported an ultrasensitive protein biomarker detection platform based on immunoassays combined with RPA. Only the DNA bound to the target in the form of a heterosandwich was selectively amplified with high specificity and sensitivity.…”
Section: Advances In Functional Nucleic Acid-based Technology To Over...mentioning
confidence: 99%
“…Research is underway to improve the sensitivity and specificity of LFAs to achieve more accurate and high-performance POCT. Such investigations have primarily focused on assay optimization (reagent and receptor) ( Dighe et al, 2022b , Dighe et al, 2022a ; Garg et al, 2021a , Garg et al, 2021b ; Grant et al, 2020b , Grant et al, 2020a ; Yu et al, 2020b , Yu et al, 2020a ; Zhang et al, 2021b , Zhang et al, 2021a ), signal amplification (chemical enhancement and electrochemistry and fluorescence reader) ( Cheng et al, 2017a , Cheng et al, 2017b ; Wang et al, 2017a , Wang et al, 2017b , 2021b ), and sample enrichment (magnetic separation and electrokinetic pre-concentration) ( Kang et al, 2021b , Kang et al, 2021a ; Wang et al, 2021aa , Wang et al, 2021ba , Wang et al, 2021ab , Wang et al, 2021bb ; Zhou et al, 2021a , Zhou et al, 2021b ) to achieve high sensitivity and selectivity ( Dempsey and Rathod, 2018b , Dempsey and Rathod, 2018a ; Han et al, 2020a , Han et al, 2020b ; Jia et al, 2018b , Jia et al, 2018a ; Li et al, 2019a , Li et al, 2019b ; Loynachan et al, 2018b , Loynachan et al, 2018a ; Mu et al, 2019b , Mu et al, 2019a ; Niu et al, 2020a , Niu et al, 2020b , Niu et al, 2021a , Niu et al, 2021b ; Ojaghi et al, 2018a , Ojaghi et al, 2018b ; Xu et al, 2014a , Xu et al, 2014b ). As one of the sample enrichment techniques, our group described a nanoelectrokinetic (NEK)-based method for sample enrichment on paper, illustrating that bovine serum albumin (BSA) can be preconcentrated by up to five times the initial concentration in serum ( Han et al, 2018b , Han et al, 2018a ; Jeong et al, 2018b , Jeong et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%